Skilled interpersonal communication : research, theory, and practice - Hargie, Owen (Routledge, 2011)
There is a fundamental, powerful, and universal desire amongst humans to interact with others. This book introduces readers to the nature of skilled interpersonal communication and reviews the main theoretical perspectives